Advanced imaging of fetal cardiac function - Kühle, Henriette; Cho, Steven K. S.; Barber, Nathaniel; Goolaub, Datta Singh; Darby, Jack R. T.; Morrison, Janna L.; Haller, Christoph; Sun, Liqun; Seed, Mike (Frontiers in Cardiovascular Medicine, 2023)
Over recent decades, a variety of advanced imaging techniques for assessing cardiovascular physiology and cardiac function in adults and children have been applied in the fetus. In many cases, technical development has been required to allow feasibility in the fetus, while an appreciation of the unique physiology of the fetal circulation is required for proper interpretation of the findings. This review will focus on recent advances in fetal echocardiography and cardiovascular magnetic resonance (CMR), providing examples of their application in research and clinical settings. We will also consider future directions for these technologies, including their ongoing technical development and potential clinical value.